2002
DOI: 10.1086/344074
|View full text |Cite
|
Sign up to set email alerts
|

The Three-dimensional Structure of the Virgo Cluster Region from Tully-Fisher and H [CSC]i[/CSC] Data

Abstract: The distances and H I contents of 161 spiral galaxies in the region of Virgo cluster are used to gain insight into the complicated structure of this galaxy system. Special attention has been paid to the investigation of the suggestion presented in an earlier work that some peripheral Virgo groups may contain strongly gas-deficient spirals.The three-dimensional galaxy distribution has been inferred from quality distance estimates obtained by averaging distance moduli based upon the Tully-Fisher relationship tak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 44 publications
5
111
0
Order By: Relevance
“…The velocity of NGC 4150 is rather low (v = 226 km s −1 ), but it is difficult to say whether it is discordant with either our distance estimate of 14.4 ± 0.7 Mpc or Karachentsev et al's (2003) ≈20 Mpc. Solanes et al (2002) have found that most Virgo galaxies in the region closest to us, corresponding to our distance to NGC 4150, have high radial velocities outward from the cluster centre (with similarly unusually high velocities away from us for Virgo cluster galaxies in the region behind the centre of the cluster). The angular separation of NGC 4150 from the cluster centre is 19 degrees.…”
Section: Discussionmentioning
confidence: 54%
“…The velocity of NGC 4150 is rather low (v = 226 km s −1 ), but it is difficult to say whether it is discordant with either our distance estimate of 14.4 ± 0.7 Mpc or Karachentsev et al's (2003) ≈20 Mpc. Solanes et al (2002) have found that most Virgo galaxies in the region closest to us, corresponding to our distance to NGC 4150, have high radial velocities outward from the cluster centre (with similarly unusually high velocities away from us for Virgo cluster galaxies in the region behind the centre of the cluster). The angular separation of NGC 4150 from the cluster centre is 19 degrees.…”
Section: Discussionmentioning
confidence: 54%
“…more than twice the distance of the Milky Way from the center of the cluster (∼17 Mpc). Solanes et al (2002), starting from the HI distribution, reconstructed the structure of the cluster, and found galaxies with elongated gas-tails, due to environmental effects, out to cluster centre distances of 25-30 Mpc. These results imply that at the distance of NGC 4189 from the cluster center it is still possible to find galaxies that are Virgo members.…”
Section: Appendix A: Notes On Individual Objectsmentioning
confidence: 99%
“…Calculation of the H I masses of these clouds is somewhat hampered by the uncertain distance of the objects. These clouds are in within the regions of the W and W structures identified by de Vaucouleurs (1961), which are farther away than the Virgo cluster proper (e.g., Solanes et al 2002). We note that the gas-rich spiral galaxy VCC297 is close to the PG1216 + 069 sight line, and the H I emission of VCC297 indicates a redshift that is quite close to the redshift of the sub-DLA and the other starless H I clouds in this field (see Figure 2).…”
Section: Starless H I Clouds In the X-ray Bright Ngc4261 Galaxy Groupmentioning
confidence: 93%
“…We note that the gas-rich spiral galaxy VCC297 is close to the PG1216 + 069 sight line, and the H I emission of VCC297 indicates a redshift that is quite close to the redshift of the sub-DLA and the other starless H I clouds in this field (see Figure 2). Thus, it is reasonable to suppose that the H I clouds are at the same distance as VCC297; the Tully-Fisher method indicates a distance of 23.4 Mpc for VCC297 (Solanes et al 2002). On the other hand, the clouds are close to the NGC4261 loose group, and they could be at the distance of the galaxy group.…”
Section: Starless H I Clouds In the X-ray Bright Ngc4261 Galaxy Groupmentioning
confidence: 98%